The use of spoon matrices in composite Class IV restorations: Penggunaan spoon matrix pada restorasi kelas IV komposit - Beatrice Fabiola; Denny Nurdin (Makassar Dental Journal PDGI Makassar, 2026)
Composite resin is often chosen as a restorative material due to its aesthetic properties and minimally invasive technique. The selection of an appropriate matrix type plays an important role in the success of the restoration. Spoon matrices are non-transparent, spoon-shaped matrices commonly used on anterior teeth to form proximal walls. A 38-year-old woman visited the Unpad Dental Hospital complaining of a black gap in her upper right anterior teeth. The patient had never received treatment for her complaint. A class IV composite restoration was performed on tooth 11 using a spoon matrix. Loss of the palatal and proximal walls required the use of a matrix to recreate the proper contour and contact of the teeth. The spoon matrix helped create a proximal wall with appropriate anatomical contours and prevented overhang. It was concluded that the use of a spoon matrix in Class IV anterior tooth restoration yielded good subjective and objective results, with appropriate anatomical contours and no overhang.